Physician autonomy and patient rights: lessons from an enforced blood transfusion and the role of patient blood management. Issue 10 (7th April 2021) - Bolcato, Matteo; Shander, Aryeh; Isbister, James P.; Trentino, Kevin M.; Russo, Marianna; Rodriguez, Daniele; Aprile, Anna
Abstract : This article provides an ethical and medico‐legal analysis of ruling no. 465 of 30 May 2018 issued by the Court of Termini Imerese (Palermo) and confirmed on appeal on 11 November 2020, which, in the absence of similar historical precedents in Europe, convicted a medical doctor of a crime of violent assault for having ordered the administration of a blood transfusion to a patient specifically declining blood transfusion on religious grounds. We analyse the Court's decision regarding the identification of assault in performing the blood transfusion and its decision not to accept exculpatory urgent 'necessity' as a defence. In addition, we present an updated revision of the current standard of care in transfusion medicine as well as the ethical principles governing the patient's declining of transfusion. In doing so, we highlight that respect for the patient's self‐determination in declining transfusions and respect for the professional autonomy of the doctor protecting the safety and life of the patient could be equally satisfied by applying the current peer‐reviewed evidence.